Correlation between leptin and the health of the gingiva: A predictor of medical risk - Vidhya Gangadhar; Amitha Ramesh; Biju Thomas (Wolters Kluwer Medknow Publications, 2011)
Context: Over the past decade, a growing body of scientific evidence has suggested an exquisite association between oral infection and systemic diseases (e.g. atherosclerosis, cardiovascular diseases, premature or low birth weight babies, pulmonary diseases, etc.) and also between systemic diseases (e.g. arthritis, diabetes, HIV infection and osteoporosis) and oral and craniofacial diseases and disorders. Leptin is a hormone secreted by the adipocytes in varying quantities and regulates the body weight. The present study was undertaken in the context of knowing the role of leptin in the inflammatory process occurring in the gingiva as the disease progressed from gingivitis to periodontitis. Aims: The present study was done to correlate the concentrations of leptin and interleukin (IL)-6 within the gingiva in healthy, gingivitis and periodontitis groups of patients and to correlate gingival leptin and IL-6 concentrations with plasma leptin and IL-6 concentrations in the healthy, gingivitis and periodontitis groups of patients. Settings and Design: This was a cross-sectional study and was carried out on the patients from the out-patient department of Periodontics in A B Shetty Memorial Institute of Dental Sciences. Patients and Methods: Seventy-five patients in the age group of 18-60 years were selected and grouped based on the gingival index (Loe and Sillness) and their clinical attachment levels into healthy, gingivitis and periodontitis groups. Leptin and IL-6 levels were estimated within gingiva and the plasma of each subject using an enzyme-linked immunosorbent assay kit. The results of this study were tabulated and subjected to statistical analysis. Mean and the standard deviation were calculated using analysis of variance Fisher's F-test and then the results were subjected to Tukey's Honest significance difference method for multiple comparison among the three groups. Correlation among the three groups was estimated using Pearson's correlation analysis. Results: Results showed a statistically significant decrease in the concentration of gingival leptin and a statistically significant increase in the concentration of plasma leptin as the gingival disease progressed. Conclusion: It was concluded that as the gingival disease progressed, the gingival leptin concentration decreased, whereas the plasma leptin concentration increased, indicating a possible correlation between leptin concentration in the gingiva and the risk of developing systemic disease like the cardiovascular disease.